1992
DOI: 10.1111/j.1365-294x.1992.tb00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality in a natural population of bacteria–Bacillus subtilis challenges the clonal paradigm

Abstract: Reproduction by binary fission necessarily establishes a clonal genotypic structure in bacterial populations unless a high rate of genetic recombination opposes it. Several genetic properties were examined for a wild population of Bacillus subtilis in the Sonoran Desert of Arizona to assess the extent of recombination in a natural population. These properties included allozyme variation revealed by multilocus enzyme electrophoresis, phage and antibiotic resistance, and restriction fragment length polymorphism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
104
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 47 publications
0
104
1
Order By: Relevance
“…Four ETs were each recovered more than nine times and a single genotype, ET 1, accounted for 15.4% of the ETs. In B. subtilis populations the most frequent ET accounted for only 3 YO of the types (Istock et al, 1992).…”
Section: Genetics Of N Gonorrhoeae Populationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four ETs were each recovered more than nine times and a single genotype, ET 1, accounted for 15.4% of the ETs. In B. subtilis populations the most frequent ET accounted for only 3 YO of the types (Istock et al, 1992).…”
Section: Genetics Of N Gonorrhoeae Populationsmentioning
confidence: 99%
“…However, B. subtilis populations reveal only modest clonal structure (Istock et al, 1992), and a recent statistical analysis of electrophoretic data has revealed that population structures can range from strictly clonal to panmictic (Maynard Smith et al, 1993). An intermediate type of population structure has also been recognized in which the population is panmictic in the long term, but occasionally a highly successful ET arises, which spreads rapidly to produce a degree of linkage disequilibrium in the population.…”
Section: Genetics Of N Gonorrhoeae Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…with pathogens like Helicobacter pylori, Neisseria gonorrhoeae, Neisseria meningitidis and Streptococcus pneumoniae, and saprophytic bacteria including Bacillus subtilis and Burkholderia cepacia on the grounds of multilocus enzyme electrophoresis or multilocus restriction typing analyses (Duncan et al, 1994 ;Go et al, 1996 ;Haubold et al, 1998 ;Istock et al, 1992 ;Maynard Smith et al, 1993 ;Mu$ ller-Graf et al, 1999 ;Wise et al, 1995). Genetic diversity created by recombination may help adapt these organisms to adverse environmental conditions or help them overcome a host's defence mechanisms (Robertson & Meyer, 1992).…”
Section: Introductionmentioning
confidence: 99%